Assessment of the impact of power business intelligence on adenoma detection rate: a prospective observational trial - Ya-Hui Hsu; Chia-Hsin Cheng; Ping-Hung Ko; Chia-Pei Tang; Chih-Wei Huang; Chih-Wei Tseng (BMC Gastroenterology)
Abstract Background Adenoma detection rate (ADR) is a key quality indicator in colonoscopy, with low ADRs linked to higher risks of post-colonoscopy colorectal cancers. Feedback to endoscopists has been shown to improve ADRs; however, many feedback systems lack automation and real-time interactivity. This study evaluates the effectiveness of Power Business Intelligence (Power BI) on ADR enhancement. Methods This prospective observational study compared ADRs before (2021) and after (2022) the implementation of Power BI at Dalin Tzu Chi Hospital, Taiwan. Power BI automatically processed pathology data to calculate ADRs and provided real-time visual feedback on endoscopy quality indicators. A total of 4,306 colonoscopies performed by 10 endoscopists were analyzed. Logistic regression was employed to identify factors associated with ADR. Results The overall ADR was high and comparable between the periods without and with Power BI (50.1% vs. 47.9%, P = 0.152). Individual performance was stable, though one low-performing endoscopist improved ADR by 20.0%. Adjusted multivariate analysis found no association between Power BI and ADR. Higher ADRs correlated with male gender (odds ratio [OR], 1.638; 95% confidence interval [CI], 1.438–1.864; p < 0.001), advanced age (OR, 1.642; CI, 1.439–1.875; p < 0.001), elevated BMI (OR, 1.642; CI, 1.439–1.875; p < 0.001), and positive stool occult blood (OR, 1.829; CI, 1.545–2.167; p < 0.001). Effective technical practices for improving ADRs included polyethylene glycol preparation (OR, 1.246; CI, 1.063–1.462; p = 0.007), water-method colonoscopy (OR, 1.321; CI, 1.134–1.538; p < 0.001), and withdrawal times ≥ 6 min (OR, 6.370; CI, 5.179–7.837; p < 0.001). Conclusions The use of Power BI was not associated with a higher ADR at a high-performing institution but may benefit low-performing endoscopists. Efforts should target behavioral changes in modifiable technical factors to drive meaningful ADR improvements.